THE INFLUENCE OF PLANNED PERCUTANEOUS CORONARY INTERVENTIONS ON MORTALITY IN TYUMEN REGION - V. A. Kuznetsov; E. I. Yaroslavskaya; G. S. Pushkarev; I. P. Zyryanov; I. S. Bessonov; Yu. S. Baranova; A. M. Polyakov; A. M. Nyamtsu (Российский кардиологический журнал, 2015)
Aim. To reveal and evaluate the relations of mortality of patients in Tymen region (non including autonomic districts) and amount of planned PCI during 2004-2012yy. period.Material and methods. We used the data on the quantity of planned PCIs that we were provided with by the departments of interventional centers ofTyumenCardiologicalCenterandTymenRegionClinicalHospital№1, and the data on mortality and morbidity, published in statistical reports of the Healthcare department of Tyumen Region.Results. During the studied period in the south ofTyumenregion there was progressive decline of mortality and significant decrease of planned PCI. We found highly relevant negative high-power correlations between the quantity of planned PCI and parameters general mortality (r=-0,98, р<0,001), general economically active mortality (r=-0,98, р<0,001) and CVD mortality (r=-0,90, р<0,001). The quantity of planned PCI showed strong significant negative correlations with the dynamics of economically active subjects mortality from CVD (r=-0,72, р=0,003) and economically active male CVD mortality (r=-0,73, р=0,020). There was a tendency for negative correlation for the quantity of planned PCI and mortality of economically active inhabitants from myocardial infarction (MI) (r=-0,67; p=0,050) and strong negative significant correlation of the quantity of planned PCI and mortality of economically active males from MI (r=-0,70, р=0,040).Conclusion. Our data points that the decrease of general and cardiovascular mortality of the south Tyumen region inhabitants is mostly relaten to a progressive increase of the amount planned PCI during 2004-2014yy